1987
DOI: 10.3109/10731198709118515
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Immunoglobulin (IG) Treatment in Prophylaxis of Bacterial Peritonitis in Capd

Abstract: To evaluate peritoneal immunological defences and to find a possible cure for alterations in the mechanism, we studied the capacity of peritoneal dialysis effluent (PDE) to opsonize bacteria and the phagocytic activity of peritoneal macrophages (PM). Subjects were 40 uremic patients followed for a mean period of 36 months and 40 normal women who underwent laparoscopy (Controls). Opsonic capacity for S.epidermidis of undiluted PDE from CAPD patients with low peritonitis occurrence (LPI) proved similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…We hypothesize that slow initial peritoneal transport rates of serum proteins result in lower dialysate concentrations of IgG, and likely a lower opsonic activity, which is a risk factor for peritonitis. This is supported by the findings of Lamperi et al (33). These authors found a significant correlation between the opsonization capacity for bacteria and IgG concentrations in peritoneal effluent.…”
Section: Discussionsupporting
confidence: 80%
“…We hypothesize that slow initial peritoneal transport rates of serum proteins result in lower dialysate concentrations of IgG, and likely a lower opsonic activity, which is a risk factor for peritonitis. This is supported by the findings of Lamperi et al (33). These authors found a significant correlation between the opsonization capacity for bacteria and IgG concentrations in peritoneal effluent.…”
Section: Discussionsupporting
confidence: 80%
“…sponsible for 5 to 10% of CAPD-related and 24% of acute community-acquired perforating appendicitis infections (21), and it is a pathogen of particular clinical concern due to its increasingly frequent antibiotic-resistant forms that are emerging during treatment with broad-spectrum antibiotics, its late complications, and its high morbidity (21). In 1986, Lamperi and coworkers reported that the local application of pooled human IgG (SRK-Ig [Swiss Red Cross]; pooled IgG from volunteers) as an intra-abdominal dialysate lavage treatment was beneficial against certain forms of peritonitis (17,25,26). The current study shows that locally delivered pooled human IgG significantly increases the survival of all IgG-treated groups in a dose-dependent manner against different challenges of multiple P. aeruginosa strains and in different strains of mice compared to control treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing emergence of antibiotic is a resistant bacteria coupled with increasing immunocompromised and elderly patient populations significant incentives prompting development of new anti-infective therapies. Among many therapeutic approaches, the use of systemic intravenous immunoglobulins (IVIG) has shown promising but inconsistent results in preventing P. aeruginosa and other bacterial infections (4,5,7,20,25,26,29,42,43). Early studies reported therapeutic benefit against CAPD-associated peritonitis by using pooled human immunoglobulin G (IgG) added directly to dialysate fluid (17,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intraperitoneal immunoglobulin has been administered prophylactically to CAPD patients, resulting in increased opsonic activity in dialysate and a reduction in the frequency of peritonitis (19). One patient with high antibody activity paradoxically suffered repeated infection, but this patient was known to comply poorly with her training in aseptic technique and dialysis exchange, and this may explain the recurrent infection.…”
Section: Patientsmentioning
confidence: 99%